Humans 40,000 y ago developed a system of conventional signs - Christian Bentz; Ewa Dutkiewicz (Proceedings of the National Academy of Sciences, 2026)
As humans, we store and share information. This allows us to distribute knowledge necessary for survival and to coordinate large groups. Our hominin ancestors harnessed the surfaces of mobile artifacts and cave walls as information carriers since the Paleolithic time period. Theories abound as to the meaning and function of these Paleolithic signs. However, very little is known about their basic, measurable properties. We here analyze a corpus of more than 200 mobile objects of a 43,000 to 34,000 y old Aurignacian culture—associated with the first modern humans to settle in Central Europe. These objects are adorned with several thousand geometric signs. We apply classification algorithms and statistical models to capture their quantitative properties. First, our analyses illustrate that these sign sequences are clearly distinguishable from modern day writing. Second, however, their statistical properties are comparable to sign sequences on the earliest protocuneiform tablets. Third, Paleolithic signs were systematically applied to yield higher information density on certain types of objects, e.g. ivory figurines compared to tools. These results cannot be taken to strictly prove that Aurignacian sign sequences encoded numero-ideographic information as in the case of protocuneiform. However, they prove that the first hunter-gatherers arriving in Europe already applied sign sequences of comparable complexity in a deliberate, systematic, and conventional manner—several ten thousand years before the advent of genuine writing.